2018
DOI: 10.1159/000493779
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation Influences Methylation Reprogramming and Delays Onset of DNA Replication in Both Pronuclei of Mouse Zygotes

Abstract: Although an essential component of assisted reproductive technologies, ovarian stimulation, or superovulation, may interfere with the epigenetic reprogramming machinery during early embryogenesis and gametogenesis. To investigate the possible impact of superovulation particularly on the methylation reprogramming process directly after fertilization, we performed immunofluorescence staining of pronuclear (PN) stage embryos with antibodies against 5mC and 5hmC. PN stage embryos obtained by superovulation display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…An increased incidence of abnormal methylation and hydroxymethylation patterns has been observed in both maternal and paternal pronuclear DNA in zygotes obtained by superovulation. Although no differences in the expression of Tet1 , Tet2 , and Tet3 genes were observed, a delay in the onset of DNA replication was induced by superovulation (Diken et al, ). Gonadotropin stimulation has also been associated with epimutations in somatic tissues and delayed epigenetic reprogramming in spermatogenic cells in the offspring (de Waal et al, ).…”
Section: Embryonic Responses To Art‐induced Stress In the Mouse Modelmentioning
confidence: 99%
“…An increased incidence of abnormal methylation and hydroxymethylation patterns has been observed in both maternal and paternal pronuclear DNA in zygotes obtained by superovulation. Although no differences in the expression of Tet1 , Tet2 , and Tet3 genes were observed, a delay in the onset of DNA replication was induced by superovulation (Diken et al, ). Gonadotropin stimulation has also been associated with epimutations in somatic tissues and delayed epigenetic reprogramming in spermatogenic cells in the offspring (de Waal et al, ).…”
Section: Embryonic Responses To Art‐induced Stress In the Mouse Modelmentioning
confidence: 99%
“…Some studies reported an increase of the rate of embryo aneuploidy and fetal malformation by use of gonadotropins 13 17 , while others contradicted these findings 4 , 18 , 19 . Some studies linked the superovulation to a direct effect on the acquisition of DNA methylation in oocytes 20 24 , including epimutations 25 , while other studies found no such effect 26 , 27 . In two studies that correlated oocyte diameters to oocyte maturity and DNA methylation 28 , one study suggested that superovulation results in smaller immature oocytes that have not completed the acquisition of DNA methylation 29 , whereas the other study found that oocyte diameters do not differ between superovulation and natural ovulation 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported an increase of the rate of embryo aneuploidy and fetal malformation by use of gonadotropins [13][14][15][16][17] , while others contradicted these findings 4,18,19 . Some studies linked the superovulation to a direct effect on the acquisition of DNA methylation in oocytes [20][21][22][23][24] , including epimutations 25 , while…”
mentioning
confidence: 99%
“…In addition, exogenous hormone stimulation contributes to epigenetic changes in oocytes and developing embryos. One study has shown that murine embryos conceived after superovulation may have superovulation‐induced DNA lesions and reduced viability, 22 whereas another found that hydroxymethylation and methylation in both the maternal pronucleus and paternal pronucleus of the zygote and the onset of zygotic DNA replication are delayed in IVF cycles 23 . Fauque et al 24 showed that superovulation disrupted H19 gene expression in individual embryos and that developmental kinetics and methylation of the H19 imprinting control region were affected by ART.…”
Section: Discussionmentioning
confidence: 99%